(untitled) (Вісник: Міжнародні відносини, 2025)
Introduction. The emergence of central bank digital currencies (CBDCs) and cryptocurrencies – forms of money instantiated as code – has catalysed a foundational reappraisal of monetary ontology. Classical theory draws a distinction between the ontic status of money (what money is) and its ontological conditions (how it becomes socially recognised as such). Tokenisation disrupts this distinction by embedding monetary functions within programmable digital architectures. This study interrogates how the advent of tokenised value and programmable money compels a reassessment of monetary being, with particular attention to their implications for currency internationalisation. Methods. The study employs a qualitative mixed-method design combining theoretical modelling and comparative case analysis. A conceptual framework – the functional continuum of moneyness – is developed using a three-dimensional metric based on the classical functions of money. Documentary analysis of monetary theory and international practice supports the framework, while comparative case vignettes (e.g., e-CNY, Onyx, e-Naira) illustrate institutional variation. Results. Findings reveal that tokenisation collapses the traditional dichotomy between monetary sign and payment infrastructure, rendering transference a built-in function of digital money. Smart contracts and protocol-layer enforcement facilitate autonomous execution of monetary rules – an emergent phenomenon described here as programmable sovereignty. The study presents a typology of ledger architectures – ranging from permissionless public blockchains to account-based state systems – each exhibiting distinct implications for trust, composability, and cross-border reach. Institutional preconditions for international circulation are analysed across legal, governance, interoperability, and privacy dimensions. Crucially, the research formulates a hypothesis: a cryptocurrency that functionally matches or exceeds the “moneyness” of the weakest recognised fiat currency may be deemed money in the global domain, regardless of state endorsement. Conclusions. Digitisation reconstitutes money as a programmable institutional object, expanding the ontological spectrum of what may qualify as currency. However, the potential for international scale depends on whether digital tokens meet key institutional thresholds: legal recognition or toleration abroad, credible governance, technological interoperability, and alignment between privacy protections and regulatory compliance. The framework developed herein offers a theoretical basis and testable propositions for evaluating the internationalisation trajectories of digital monies, including their capacity either to circumvent or to become embedded within existing global monetary hierarchies.